Evaluation of the schistosomiasis control program (PCE) in an endemic area, northeastern Brazil: a population-based and 10-year time series study - Menezes Santos de Jesus, Damyres; do Rosário Souza, Mariana; dos Santos, Allan Dantas; Bezerra-Santos, Márcio; Gomes Machado de Araújo, Karina Conceição (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
Schistosomiasis is an endemic disease in Brazil and the State with the highest positive rate in the country is Sergipe. Herein, we assessed data from the Brazilian Schistosomiasis Control Program (PCE) in the State of Sergipe between the period 2008 and 2017. We evaluated data about schistosomiasis and snails of the genus Biomphalaria. We used the log-linear regression model (joinpoint) to assess temporal trends and the Kernel estimator for spatial statistics analysis. According to the PCE, Sergipe has 51 endemic municipalities for schistosomiasis. Nevertheless, information about the disease and that collected by the PCE has not been recorded regularly in all endemic municipalities. Additionally, only nine municipalities (17.6%) carried out the malacological survey. The average of positive rate from schistosomiasis in Sergipe was 8.4%. However, our data suggest that it may be underestimated. The spatial analysis maps (Kernel maps) showed areas of high transmission of the disease in municipalities close to the São Francisco River and in the metropolitan region of the State. Altogether, our findings suggest that schistosomiasis has been underreported and it is still a serious public health concern in Sergipe. In addition, there are significant failures in the conduction of PCE’s activities by the municipalities. KEY WORDS: Schistosomiasis; Epidemiological monitoring; Spatial analysis; Brazil.